Characterization of isomeric glycan structures by LC‐MS/MS. Issue 17 (17th May 2017) - Veillon, Lucas; Huang, Yifan; Peng, Wenjing; Dong, Xue; Cho, Byeong Gwan; Mechref, Yehia
Abstract: The characterization of glycosylation is critical for obtaining a comprehensive view of the regulation and functions of glycoproteins of interest. Due to the complex nature of oligosaccharides, stemming from variable compositions and linkages, and ion suppression effects, the chromatographic separation of glycans, including isomeric structures, is necessary for exhaustive characterization by MS. This review introduces the fundamental principles underlying the techniques in LC utilized by modern day glycomics researchers. Recent advances in porous graphitized carbon, reverse phase, ion exchange, and hydrophilic interaction LC utilized in conjunction with MS, for the characterization of protein glycosylation, are described with an emphasis on methods capable of resolving isomeric glycan structures.